Amazonian ecoethos: An educational resource for simulating socioenvironmental dilemmas in environmental education - Higuchi, Maria Inês Gasparetto; Azevedo, Genoveva Chagas; Alves, Iris Rianne Santana (Desenvolvimento e Meio Ambiente, 2019)
“Amazonian Ecoethos” was created to meet the needs of more efficient and effective educational resources for Environmental Education in school and non-school contexts with the young public. “Amazonian Ecoethos” is a simulation game that involves the participants in an interactive, exciting and playful journey through socioenvironmental dilemmas confrontation and cooperative search for solutions. This study describes the game and includes the perception of teachers who accompanied the experience of the game that their students had. We used semi-structured interviews with 15 teachers of the 6th to the 9th grade of elementary public schools in Manaus (Amazon state) to verify the potentialities of the game using the theoretical and methodological assumptions of User Experience (UX). The results obtained from the content analysis pointed out that in the teachers’ perception, Ecoethos achieves the educational objectives that were proposed, such as the understanding and application of knowledge through situations that simulate socioenvironmental reality. Learning centered on cooperative decision making, interactivity and playfulness was central to experiences that allowed the participants to immerse themselves in the educational task and to reflect on their daily behavior. These results indicate the Ecoethos as a valuable educational tool to the teaching-learning process and to the development of youths’ socio-environmental responsibility. © 2019 Universidade Federal do Parana. All rights reserved.
Ecoethos da Amazônia: um recurso didático para simulação de dilemas socioambientais na educação ambiental